I-Globe (Interactive Globe) android based application - Parameswari, Ranganathan (Universiti Malaysia Sarawak (UNIMAS), 2014)
In this modem era, everyone tend to take less importance in general knowledge about their surroundings. As for a great example, most of us do not know about the places of wonders in this world and types of wonders that are available. To solve this, I-Globe (Interactive Globe) which is an Android Application is developed for the aims to serve as an interactive learning repository to users to experience about places of wonders. It enables users to play a game of answering question that will ask them about the wonder places and present the information on the wonder places to them with the images of those places. This application is an application that focuses on Wonders places which are 7 New Wonders of World and 7 New Wonders of Nature. It is an educational application that has globe applications for user to find location of those wonders places in world. With this application, user should be able to navigate through the location of places of wonders in world. The main objective is to enable people to enable people to have some historical and geographical knowledge regarding these wonders using this mobile application and increase their interest in this topic. Besides it provide a package of information gaining elements.